GENETIC VARIABILITY STUDIES FOR DIFFERENTIAL SOIL PHOSPHORUS CONTENT IN RICE (ORYZA SATIVA L.) - R. GOBINATH; C. GIREESH, N. MADHUSUDAN, K.V. RADHAKRISHNA, P. SENGUTTUVEL, R.M. SUNDARAM (The Journal of Research, PJTSAU, 2020)
Rice is a self-pollinated cereal crop belonging to the family Gramineae (synomym-Poaceae) under the order Cyperales and class Monocotyledon having chromosome number 2n=24. Rice is the second largest produced cereal in the world in 158.3 million hectare area with annual production of about 685.24 million metric tons (Roy.et al.,2001) and also the staple food for over one third of the world’s population (Siva Subramanian et al., 1973).